Factors associated with hepatitis C antibody seroconversion after transplantation of kidneys from hepatitis C infected donors to hepatitis C naïve recipients. Issue 1 (1st January 2020) - Agbim, Uchenna; Cseprekal, Orsolya; Yazawa, Masahiko; Talwar, Manish; Balaraman, Vasanthi; Bhalla, Anshul; Podila, Pradeep S. B.; Maliakkal, Benedict; Nair, Satheesh; Eason, James D.; Molnar, Miklos Z.
Abstract: Background: We aimed to assess the probability and factors associated with the presence of hepatitis C virus (HCV) antibody among HCV seronegative kidney transplant recipients receiving HCV-infected (nucleic acid testing positive) donor kidneys. Methods: This is a retrospective review examining HCV antibody seroconversion of all kidney transplant recipients receiving an organ from an HCV-infected donor between 1 March 2018 and 2 December 2019 at a high-volume kidney transplant center in the southeast United States. Results: Of 97 patients receiving HCV-infected kidneys, the final cohort consisted of 85 recipients with 5 (5.9%) recipients noted to have HCV antibody seroconversion in the setting of HCV viremia. The HCV RNA level at closest time of antibody measurement was higher in the seroconverted patients versus the ones who never converted [median and (interquartile range): 1, 091, 500 (345, 000–8, 360, 000) vs 71, 500 (73–313, 000), p = 0.02]. No other significant differences including type of immunosuppression were noted between the HCV antibody positive group and HCV antibody negative group. Donor donation after cardiac death status [Odds Ratio (OR) and 95% Confidence Interval (CI) was: 8.22 (1.14–59.14)], donor age [OR (95% CI) (+5 years) was: 3.19 (1.39–7.29)] and Kidney Donor Profile Index [OR (95% CI) (+1) was:1.07 (1.01–1.15)] showed a statistically significant association with HCV seroconversion. Conclusions: HCV antibody should not be considered routine screening for presence of infection in previously HCV naïve kidney transplant recipients receiving kidneys from HCV-infected donors, as only a modest percentage have antibody despite active viremia. The assessment of HCV viral load should be routine in all transplant recipients receiving organs from public health service increased risk donors.